Cost-effectiveness analysis of the vaccination program against bovine brucella abortus in the department of nariño (2012)
Objective: A cost-effectiveness analysis was conducted for the control and eradication program of bovine Brucellosis using the vaccine against strain 19 in the Department of Nariño (Colombia). Materials and methods: A cost-effectiveness study was conducted using a deterministic model with a hypothetic cohort of 100.000 animals, the time horizon was from the time of vaccination until the animals go into production (24 months). A model of the natural history of disease was constructed with data extracted from literature review, the costs were established from the perspective of SAGAN in 2008, the lowest effectiveness figure for the vaccine was used with a conservative illness scenario, and a sensitivity analysis was performed for the prevalence variables, milk price, and the cost and coverage of the vaccine. Results: A favorable cost-effectiveness relation for the different health outcomes analyzed within this work (Abortions, temporal infertility, mortality, prenatal mortality, milk and meat Production) was found. Conclusions: The Brucellosis control and eradication program in the Department Nariño against strain 19 is efficient from SAGAN's perspective; this program should count with support on the part of relevant institutions for the epidemiologic vigilance of this disease.